Preparation of a Lanthanide–Titanium Oxo Cluster–Polymer Composite by CuI‐Catalyzed Click Chemistry. Issue 2 (9th December 2020) - Deng, Yong‐Kai; Zhao, Ya‐Rui; Xu, Han; Kong, Xiang‐Jian; Long, La‐sheng; Zheng, Lan‐Sun
Abstract: Incorporating metal clusters within the skeleton of the organic polymers through a click reaction cannot only effectively prepare cluster–polymer composites, but also effectively avoid the cluster aggregation. Herein, an azide‐containing lanthanide–titanium oxo cluster of Eu8 Ti10 ‐N3 (Eu8 Ti10 ‐N3 =[Eu8 Ti10 ( μ 3 ‐O)14 (H2 O)4 (OAc)2 (tbba)30 (paza)4 (THF)2 ]⋅ 4 THF⋅ 8 H2 O (1 ), Htbba=4‐ tert ‐butylbenzoic acid, Hpaza=4‐azidobenzoate, HOAc=acetic acid, THF=tetrahydrofuran) through an in situ solvothermal reaction of 4‐azidobenzoic acid and 4‐ tert ‐butylbenzoic acid. Reaction of 1 with PEG (PEG =methoxypoly(ethyleneglycol)alkyne, 2000 g mol −1 ) through Cu I ‐catalyzed click chemistry generates a lanthanide–polymer composite of Eu8 Ti10 ‐N3 @PEG (2 ). Investigation with IR, 1 H NMR and ICP‐OES of 2 indicates that the structural integrity of 1 is maintained in 2 . Study of the luminescent properties of 1 and 2 reveals that the quantum yield of 1 itself basically remains unchanged in 2 . Significantly, the formation of 2 cannot only effectively prevent the cluster 1 from aggregation, but also greatly enhance its solubility and adhesion to the substrate. Owing to the solubility and adhesion of luminescent materials being the key to their practical application, present work is thus of great significance for the development of metal cluster–polymer composite luminescent materials. Abstract : Click reactions : Reaction of an azide‐containing lanthanide–titanium oxo cluster of Eu8 Ti10 ‐N3 (1 ) with PEG through Cu I ‐catalyzed click chemistry generates a lanthanide–polymer composite of Eu8 Ti10 ‐N3 @PEG (2 ), which exhibits excellent film‐forming and adhesion to the substrate, while the luminescent property of 1 itself basically keeps unchanged in 2 (see figure).